Development of an Importance Scale for Seawater Intake Types Based on Physical Parameters Database - El Masmodi, Rim; El Mansouri, Bouabid (E3S web of conferences, 2025)
This article presents an advanced Geographic Information Systems (GIS) based interface that innovates coastal water resource management in Morocco, with specific application to the ASSILAH region. This solution integrates spatial analysis with multi-criteria decision support, particularly focusing on the geographical distribution and territorial challenges of the Moroccan coastline, using programming tools such as Excel Visual Basic for Applications (VBA). The methodology combines GIS spatial analysis capabilities with the Analytic Hierarchy Process (AHP) to evaluate complex geographical parameters including bathymetry and coastal infrastructure. The integration of geospatial data provides a clear and precise visualization of potential areas for seawater intake installations, thereby facilitating the understanding of territorial issues for decision-makers. The AHP method, known for its robustness in multi-criteria decision support, allows for choosing the optimal type of seawater intake. The interface, developed through Excel and VBA, transforms complex spatial and analytical data into an accessible decision support tool. The resulting system offers regional planners a comprehensive framework for coastal sustainable infrastructure development in the Assilah coastal region as a pilot case for Morocco's unique geographical context.